Industrial research and development and real exchange rate depreciation in a small open economy - Tabrizy, Saleh S. (My University, 2020)
To examine how changes in relative national prices affect innovation input, this paper studies the impact of changes in industry‐specific effective real exchange rates on industrial R&D expenditures in Korea. In particular, it explores the heterogeneous responses of industries with different export intensities. Employing dynamic panel data estimation techniques, the results suggest that among industries with medium levels of export intensity a lagged depreciation in industry‐specific effective real exchange rate leads to a decline in contemporaneous industry‐level R&D expenditures. However, this adverse effect is insignificant for industries that either mostly serve the domestic markets or that are heavily engaged in foreign markets. This is a postprint of the published article.
Keywords: Exchange Rate; Export Intensity; R&D